Acetylation targets HSD17B4 for degradation via the CMA pathway in response to estrone. Issue 3 (4th March 2017) - Zhang, Ye; Xu, Ying-Ying; Yao, Chuan-Bo; Li, Jin-Tao; Zhao, Xiang-Ning; Yang, Hong-Bin; Zhang, Min; Yin, Miao; Chen, Jing; Lei, Qun-Ying
ABSTRACT: Dysregulation of hormone metabolism is implicated in human breast cancer. 17β-hydroxysteroid dehydrogenase type 4 ( HSD17B4 ) catalyzes the conversion of estradiol (E2) to estrone (E1), and is associated with the pathogenesis and development of various cancers. Here we show that E1 upregulates HSD17B4 acetylation at lysine 669 (K669) and thereby promotes HSD17B4 degradation via chaperone-mediated autophagy (CMA), while a single mutation at K669 reverses the degradation and confers migratory and invasive properties to MCF7 cells upon E1 treatment. CREBBP and SIRT3 dynamically control K669 acetylation level of HSD17B4 in response to E1. More importantly, K669 acetylation is inversely correlated with HSD17B4 in human breast cancer tissues. Our study reveals a crosstalk between acetylation and CMA degradation in HSD17B4 regulation, and a critical role of the regulation in the malignant progression of breast cancer.